Trigger Finger From Ocean Rowing: An Observational Study. (March 2022) - Welman, Ted; Young, Kieron; Larkin, Jo; Horwitz, Maxim D.
Background: Trigger finger has a prevalence of 2% to 3% in the general population. Although anecdotal evidence exists, there is a lack of conclusive data that prove a relationship between repetitive power grip and flexion with triggering. Ocean rowing is becoming a popular sport, with the race across the Atlantic alone attracting more than 100 participants annually. Anecdotal reports suggest ocean rowing may be a significant cause of trigger finger. We aimed to identify whether the sport causes an increased prevalence of triggering, whether there were any alleviating or compounding factors, and, finally, whether there was any effect on performance.Methods: A prospective observational study was carried out. A questionnaire was sent to all participants of the Talisker Whisky Atlantic Challenge 2018, which included a trigger finger self-scoring system and the Oslo Sports Trauma Center Overuse Injury Questionnaire.Results: Responses were received from 67 rowers (83% response rate). Age ranged from 21 to 62 years, with a mean of 40 years. In all, 49.3% had clinical triggering, with 79.3% reporting bilateral symptoms. The length of continuous rest time had a significant impact on the incidence of finger triggering and disease stage ( P = .0275 and .0353, respectively; multivariate logistic regression). High-grade triggering had a more negative effect on rowing performance than low grade or no triggering (not significant).Conclusion: Ocean rowers suffered a 15-fold increase in trigger finger prevalence compared with the general population. This was increased in those who took shorter, more frequent rest periods. This study provides new conclusive evidence that the repetitive power grip and flexion involved in rowing increase the prevalence of trigger finger.